Developing the next generation of quality improvers: An evaluation of a region wide structured support quality improvement training programme. (July 2016) - Bethune, Rob; Dahill, Mark; Finucane, Katherine; Van Hamel, Clare; Watson, Joanne; Woodhead, Patricia
Introduction: Despite an increasing and widespread understanding of the importance of quality improvement in healthcare, medical students and junior doctors receive variable training in improvement methods. The South West Foundation Doctor quality improvement programme attempted to equip junior doctors with the skills to develop and improve healthcare services. Methods: A questionnaire-based evaluation was undertaken of a cohort of first-year doctors who took part in a 9-month quality improvement educational intervention. The study was conducted across a whole training region with some of the hospitals running the quality improvement educational intervention and one acting as the natural control cohort. A previously validated questionnaire was sent out at the start and end of their first year. Results: In questions related to attitudes to all domains of quality improvement first-year doctors consider it an important part of their role as doctors to improve the quality of healthcare. However, they do not think they are equipped with the skills to do this improvement. During their first year as doctors, these self-reported skills increased dramatically in the hospitals that took part in the programme but not in the single hospital that did not run the programme. Conclusion: First-year doctors consider improving the quality of healthcare to be an important part of their job. This can be contrasted to their self-reported skills related to quality improvement when they start their first year. In hospitals that run a structured, supported experiential quality improvement programme, these self-reported skills increase statistically significantly.